First Report of Verticillium Wilt Caused by Verticillium dahliae Infection on Chinese Cabbage in Korea - Walftor, Dumin; Mi-Jeong, Park; Jong-Han, Park; Kyung-Sook, Han; Hyo-Won, Choi; Chang-Gi, Back (APS Publications, 2022)
Chinese cabbage (Brassica rapa L.) is an important vegetable in Korea as the main ingredient for kimchi. In June 2014, symptoms of leaf wilt, drying, and drop off were observed in a Chinese cabbage farm located at Taebeak (37°26′50.7″N, 128°95′50.0″E), Gangwon province, Korea. This disease was observed on ∼35% of plants in the field, causing an almost 10% decrease in production.